Odpowiedzi

2009-12-09T16:05:54+01:00
A)

2a² - √5 2*5² - √5 50 - √5
---------- = ----------- = -------------
2b - 9 2*(-2) - 9 -13

B)

2*7² - √5 98 - √5
---------- = -----------
2 * 3 - 9 -3
2009-12-09T16:08:55+01:00
A)
2a² - √5
------------=50-√5 50-√5 -650+13√5 -637√5
2b - 9 ------- = -------= ------------- = --------- =3,81√5
-4-9 -13 169 169


b) 2a² - √5 98-√5
------------= ---------=
2b - 9 -3
2009-12-09T16:17:05+01:00
Oblicz wartość liczbową wyrażenia
2a² - √5
------------
2b - 9

dla:
a) a=5 ; b= -2
2*5²-√5 50-√5
--------- = -------- = (50-√5):-13 = 3 11/13 + 1/13 √5
2*-2-9 -13

b) a=7; b=3
2*5²-√5 2*7²-√5 98 - √5
--------- = ---------- = ----------- = 32⅔+⅓√5
2*-2-9 2*3-9 -3